Faktor Yang Berhubungan Dengan Status Gizi Ibu Hamil di Puskesmas Aek Parombunan Kota Sibolga Tahun 2023 - Aprianingsih Situmorang; Magdalena Br Barus (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2023)
Lack of nutrients and the low level of health of pregnant women are still very vulnerable, this is indicated by the still high MMR caused by bleeding due to nutritional anemia and Chronic Energy Deficiency (CED) during pregnancy The factors causing CED in pregnant women are very complex, including imbalance in nutritional intake, infectious diseases and bleeding. This research aims to determine the factors related to the nutritional status of pregnant women at the Aek Parombunan Health Center, Sibolga City in 2023. This type of research is a survey type with a cross sectional The population in this study was all pregnant women who visited the Parombuan Community Health Center who met the requirements and were determined to be a research population of 98 people. Bivariate analysis using the Chi-square test. There is a relationship between parity and the nutritional status of pregnant women with a p-value of 0.02. There is a relationship between economic status and the nutritional status of pregnant women with a p-value of 0.03. . Pregnant women are advised to consume more balanced foods that contain the nutrients energy, protein, iron and vitamin A to avoid nutritional problems during pregnancy such as KEK, KKP, iron deficiency anemia.